1999
DOI: 10.1046/j.1365-2036.1999.00440.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pumaprazole (BY841), a novel reversible proton pump antagonist, and of omeprazole, on intragastric acidity before and after cure of Helicobacter pylori infection

Abstract: INTRODUCTIONOmeprazole, an irreversible proton pump inhibitor, produces higher intragastric pH values in the presence of Helicobacter pylori infection than after cure of the infection, both in healthy subjects 1, 2 and in patients with duodenal ulcer disease. 3 The mechanism underlying this effect is still unclear. Two possible explanations have been put forward: (1) decreased production of ammonia or other neutralizing substances after cure of the infection, 4, 5 or (2) development of body gastritis during om… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 21 publications
2
22
1
Order By: Relevance
“…For factors influencing pH, only H. pylori was significant, which confirms previous reports that H. pylori-positive patients have higher suppression effects against gastric secretion (18,19). This study found that there were no differences in baseline pH between H. pylori-positive and -negative patients, but the % time of pH >4 and >6 for 48 h showed significant differences after the use of PPI.…”
Section: Discussionsupporting
confidence: 80%
“…For factors influencing pH, only H. pylori was significant, which confirms previous reports that H. pylori-positive patients have higher suppression effects against gastric secretion (18,19). This study found that there were no differences in baseline pH between H. pylori-positive and -negative patients, but the % time of pH >4 and >6 for 48 h showed significant differences after the use of PPI.…”
Section: Discussionsupporting
confidence: 80%
“…As the present study is on the effect on the first day after a single dose of PPIs, both RPZ and LPZ are considered to be influenced by CYP2C19 genotype status. Previous reports have indicated that H pylori infection of the gastric mucosa potentiates the effects of proton pump inhibitors [40,41] . Therefore, in the present study, the study subjects were all H pylori-negative CYP2C19 EMs.…”
Section: Discussionmentioning
confidence: 99%
“…A sixth randomized study directly comparing racecadotril and loperamide in the treatment of acute diarrhea was performed in a pediatric population with a mean age of 4.7 years (range 2–10 years) in a double-blind, double-placebo design (Turck et al, 1999). Fifty-two children received 1.5 mg/kg racecadotril thrice daily and 50 received 0.03 mg/kg loperamide thrice daily.…”
Section: Studies In the Gastro-intestinal Tractmentioning
confidence: 99%